2014
DOI: 10.1111/jzo.12092
|View full text |Cite
|
Sign up to set email alerts
|

Intrapopulational variation of ejaculate traits and sperm depletion in red‐sided garter snakes

Abstract: Female sexual promiscuity is a prevalent element of mating systems. One consequence of female sexual promiscuity is that male-male competition often continues post-copulation within the female's reproductive tract. According to theory, the number of sperm a male inseminates relative to his rivals strongly predicts his fertilization success. However, sperm quality is also important, especially when males are sperm limited and female sperm storage is prevalent. In this study, we examined intrapopulational variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 73 publications
2
27
0
Order By: Relevance
“…Indeed, in redsided garter snakes, total plug mass is positively correlated with male and female size (Friesen et al, 2014c,d;Shine et al, 2000a). Males allocate more plug material, but not more sperm, to larger females, and males tend to copulate longer with larger females (Friesen et al, 2014c). We found further support in the present study for larger females receiving larger copulatory plugs, but water content has the strongest relationship with female size.…”
Section: Prudent Allocation Of Ejaculatessupporting
confidence: 79%
See 4 more Smart Citations
“…Indeed, in redsided garter snakes, total plug mass is positively correlated with male and female size (Friesen et al, 2014c,d;Shine et al, 2000a). Males allocate more plug material, but not more sperm, to larger females, and males tend to copulate longer with larger females (Friesen et al, 2014c). We found further support in the present study for larger females receiving larger copulatory plugs, but water content has the strongest relationship with female size.…”
Section: Prudent Allocation Of Ejaculatessupporting
confidence: 79%
“…Female mass did not strongly affect energy density (in kJ g −1 : R 2 =0.154, F 1,18 =3.091, P=0.097), dry plug mass (in g: R 2 =0.152, F 1,18 =3.039, P=0.099), or total energy per plug (in kJ: female mass, F 1,18 =3.704, P=0.072), but plugs from larger females contained significantly more water (in g: female mass, F 1,18 =9.897, P=0.006). We note that this study has smaller sample sizes than those that have found significant effects of male and female size on plug mass in this species (Friesen et al, 2013(Friesen et al, , 2014cShine et al, 2000a).…”
Section: Energy Content Of the Copulatory Plugmentioning
confidence: 84%
See 3 more Smart Citations